2020
DOI: 10.21203/rs.3.rs-78111/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and Drivers to Service Delivery in Global Mental Health Projects

Abstract: Background: Research within global mental health (GMH) has extensively documented how contextual factors like political instability, poverty and poorly-funded health infrastructures continue to compromise effective and equitable mental health service delivery. There is a need to develop more feasible and evidence-based solutions through implementation research. This paper, one in a series pertaining to implementation in GMH projects worldwide, focuses on implementation factors influencing mental health service… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These factors point to the importance of communication and awareness-raising about mental health and mental health services as a means of increasing engagement. Despite this fact, few of the programs included in this study included mental health promotion and awareness components [ 22 ] . This indicates a need for improved communication for mental health awareness-raising among stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors point to the importance of communication and awareness-raising about mental health and mental health services as a means of increasing engagement. Despite this fact, few of the programs included in this study included mental health promotion and awareness components [ 22 ] . This indicates a need for improved communication for mental health awareness-raising among stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Each of three members of the study team (JM, OQ and TE) initially identified themes, and subsequently discussed and refined them until consensus was achieved. This paper presents findings for the stakeholder engagement cluster, with results from the other two clusters published as part of this series [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over- or under-estimating the level of demand for services was a commonly faced barrier to successful delivery for grantees [ 23 ]. Reliance on isolated prevalence estimates [ 33 ], lack of appropriate epidemiological statistics on population mental health [ 34 ], limited understanding of the attitudes on help seeking for mental health [ 35 ], fragmented routine data around existing service use [ 36 ], and lack of validation of screening tools [ 37 ] could all be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, qualifying in advance what success at each step on the pathway should look like would also have been problematic. The variation we observed among project targets set by grantees suggests that these were not well-defined from the outset, an issue explored further in Qureshi et al [ 23 ]. Importantly, the extent to which targets were achieved did not necessarily reflect the degree to which implementation was successful.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
See 1 more Smart Citation